Case Studies from the Clinic: Initiating and Implementing Patient-Reported Outcome Measures. Issue 1 (12th June 2017) - Locklear, Tracie; DeBar, Lynn L.; Willig, James; Rundell, Sean; Blackhall, Leslie; Zatzick, Douglas; Staman, Karen; Bhavsar, Nrupen; Weinfurt, Kevin; Abernethy, Amy P
Introduction: Self-reporting by patients though the use of electronic patient-reported outcome (PRO) measures has been shown to use increase patient satisfaction with care, and improve patient-provider communication, symptom management, and health quality. Additionally, PROs are increasingly used in research to expand understanding regarding the relative risks, benefits, and burdens of interventions. While experience embedding patient-reported outcomes (PROs) into registries and clinical workflow is growing, there is little in the literature to guide those interested in incorporating PROs into routine clinical care and for use in research. Case Descriptions: The NIH Health Care Systems Research Collaboratory PRO Core interviewed investigators from seven programs to get their first-hand experiences on the incorporation of PROs for both care and research, and the investigators have contributed to this manuscript as authors. Findings: We use these case studies to present practical approaches to initiating and implementing PROS, including instrument selection, tips for integrating PRO collection systems into clinical workflow, considerations for user experience and data collection, and the methods to assess and monitor quality. Conclusion: Because the decision to initiate and implement PRO collection impacts many different stakeholders, the solution requires collaboration among the involved parties, careful planning, and integration into clinical workflow.